Unique therapeutic potentialities of exosomes based nanodrug carriers to target tumor microenvironment in cancer therapy - Safir Ullah Khan; Munir Ullah Khan; Yanyan Gao; Muhammad Imran Khan; Sabah Mushtaq Puswal; Muhammad Zubair; Muhammad Ammar Khan; Rahat Farwa; Shuang Gao; Rizwan Ali; Nazim Hussain (Elsevier, 2022)
Cancer is a complex syndrome with a high mortality rate worldwide due to the lack of effective treatments. The lack of effective coordination between tumor cells and immune system components may be an important reason for the failure of tumor cells to be successfully eliminated after treatment. Tumor microenvironment (TME) barriers hinder the entry and dispersion of nanotherapeutic medicines in tumors. Extracellular vesicles (EVs) are membrane-bound structures responsible for cell-to-cell coordination and carry different biomolecules responsible for physiological and pathological communication between cells. Their role has been a mystery for decades, and over the past two decades, their structure and content have revealed some amazing facts.Recent studies have shown that exosomes play a key role in intercellular communication during the pathogenesis of diseases such as cancer and are responsible for cancer proliferation and metastasis. Inspired by the structure of their endogenous lipid membranes, researchers have tried to mimic their fine structure in the laboratory and tried to load certain biological and chemical drugs. Therefore, exosomes have received particular attention in nanotechnology, and these lipid polymeric micelles have emerged as potential candidates for nanocarriers in nanotechnology to overcome various obstacles in targeted drug delivery. In view of the importance of exosomes, this review highlights the potential of exosomes for use in nanodrug-based medication delivery. The majority of the investigation in these fields has not yet moved out of the laboratory. It will take a lot of time and work to implement these experimental findings in clinical settings.